LAJU SEDIMENTASI DI PERAIRAN KURAU, KABUPATEN BANGKA TENGAH - Rismawati; Aditya Pamungkas; Mohammad Agung Nugraha (UNU Purwokerto, 2022)
The estuary of the Kurau Watershed (DAS) has domestic activities. The problem that commonly occurs in river mouths is the emergence of sediment, which causes disruption of water flow upstream and can cause flooding. Kurau waters have considerable water resources, but it is also decreasing year on year. This study aimed to determine the sedimentation rate, TSS, and the type of sediment texture in Kurau waters, Central Bangka. Sedimentation rate data was obtained using a sediment trap. Analysis of TSS (Total Suspended Solid) and sediment texture using gravimetric and pipette methods. The sedimentation rate in Kurau waters is not high based on weight, namely 0.03-0.14 mg/cm²/day, and volume with a value range of 0.13-0.58 cm/day. The concentration of TSS on the surface of Kurau waters based on PP no. 22/2021 has not passed the seawater quality standard with a TSS concentration of 0.03-0.04 mg/L. Kurau waters have various types of sediment texture, namely sand with a percentage ranging from 6.54-78.33%, dust with a percentage of 14.72-45.74%, and clay with a percentage of 6.94-47.72%. The sedimentary textures in Kurau waters are dusty clay, loamy sand, and loamy clay.